Transition from asymmetric to symmetric regulation of competition in the electronic communications sector in Bulgaria - Sulev, Georgi (Yearbook Telecommunications, 2021)
In the electronic communications sector, the regulation of undertakings with significant market power is described as "asymmetric regulation" to indicate that obligations are imposed only on companies with leading position. The asymmetric regulation is subject to periodic review with a view to its complete abolition and replacement by the application of competition law. "Symmetric regulation" applies to all undertakings, regardless of their market position, and includes obligations to interconnect their networks, provide access to network elements, physical infrastructure, numbers, services and databases. From 2021, symmetric regulation is going to be the main method for ensuring and protecting competition in electronic communications markets in Bulgaria.